The Philadelphia Shriners Hospital Approach to Brachial Plexus Birth Injury - Gundlach, Benjamin; Kozin, Scott H.; Zlotolow, Dan A.; Park, Eugene (Seminars in Plastic Surgery, 2023)
The care of children with brachial plexus birth injuries (BPBI) is a complex multidisciplinary endeavor. At the Shriners Hospital for Children in Philadelphia, we have sought to elevate the quality of care delivered to patients through outcomes research and collaboration with colleagues around the world. Our approach to the management of this challenging pathology has evolved time and again. Here, we describe our current approach to patient assessment and operative management in patients with BPBI and its many sequelae.
Keywords: brachial plexus birth palsy; nerve grafting; nerve transfers; Erb's palsy; contralateral C7 transfer